Evolution of the prevalence of hepatitis C virus infection and hepatitis C virus genotype distribution in human immunodeficiency virus-infected patients in Italy between 1997 and 2015. (April 2018) - Rossetti, B.; Bai, F.; Tavelli, A.; Galli, M.; Antinori, A.; Castelli, F.; Pellizzer, G.; Cozzi-Lepri, A.; Bonora, S.; Monforte, A.d'Arminio; Puoti, M.; De Luca, A.; et al.
Abstract: Objectives: To analyse the variation of hepatitis C virus (HCV) prevalence and genotype distribution and their determinants in people living with human immunodeficiency virus (HIV) who entered care between 1997 and 2015. Methods: HIV-infected patients enrolled in ICONA who were tested for HCV antibodies (HCV-Ab) were included. Results: Overall 3407 of 12 135 (28.1%) were HCV-Ab+; and 735 of 12 135 (6.1%) were HBsAg+. Among patients whose HCV genotype was known, the most represented were genotypes 1 and 3. The prevalence of HCV infection decreased from 49.2% (2565/5217) during 1997–2002 to 10.2% (556/5466) during 2009–2015. The frequency of genotype 1a increased from 29.0% (264/911) to 43.0% (129/300), whereas genotype 3 decreased from 38.5% (351/911) to 27.0% (81/300). Independent predictors of HCV-Ab+ status were being female (adjusted OR (AOR) 1.23, 95% CI 1.04–1.50, p = 0.01), risk category (versus injecting drug users: men who have sex with men AOR 0.01, 95% CI 0.01–0.01, p <0.001; heterosexuals AOR 0.01, 95% CI 0.01–0.01, p <0.001; other/unknown AOR 0.02, 95% CI 0.01–0.02, p <0.001), being cared for in Central Italy (versus being cared for in Northern Italy: AOR 0.85, 95% CI 0.73–0.98, p <0.001), being Italian-born (AOR 1.44, 95% CI 1.16–1.80, p = 0.001) and being enrolled in less recent calendar years (versus 1997–2002: 2009–2015 AOR 0.23, 95% CI 0.19–0.27, p <0.001; 2003–2008 AOR 0.49, 95% CI 0.41–0.61, p <0.001). Conclusions: The prevalence of HCV infection in HIV-infected patients entering into care in Italy significantly declined in more recent calendar years. After adjusting for risk factors and calendar years, HCV co-infection was more frequent in females and in those born in Italy.